Comprehensive Pathogen Identification, Antibiotic Resistance, and Virulence Genes Prediction Directly From Simulated Blood Samples and Positive Blood Cultures by Nanopore Metagenomic Sequencing - Zhou, Menglan; Wu, Yarong; Kudinha, Timothy; Jia, Peiyao; Wang, Lei; Xu, Yingchun; Yang, Qiwen (Frontiers in Genetics, 2021)
Bloodstream infection is a major cause of morbidity and mortality worldwide. We explored whether MinION Nanopore sequencing could accelerate diagnosis, resistance and virulence profiling prediction in simulated blood samples and blood cultures. One milliliter of healthy blood samples from direct spike (sample 1), anaerobic (sample 2) and aerobic (sample 3) blood culture with initial inoculation of ~30 CFU/ml of a clinically isolated Klebsiella pneumoniae strain, were subjected to DNA extraction and Nanopore sequencing. Hybrid assembly of Illumina and Nanopore reads from pure colonies of the isolate (sample 4) was used as a reference for comparison. Hybrid assembly of the reference genome identified a total of 39 antibiotic resistance genes and 77 virulence genes through alignment with the CARD and VFDB database. Nanopore correctly detected K. pneumoniae in all three blood samples. Fastest identification was achieved within 8h from specimen to result in sample 1 without blood culture. However, direct sequencing in sample 1 only identified seven resistance genes (20.6%) but 28 genes in sample 2-4 (82.4%) compared to reference within 2h sequencing time. Similarly, 11 (14.3%) and 74 (96.1%) of the virulence genes were detected in sample 1 and sample 2-4 within 2h sequencing time, respectively. Direct Nanopore sequencing from positive blood cultures allowed comprehensive pathogen identification, resistance and virulence genes prediction within 2h which is promising to be used in point-of-care clinical settings.